ASPEK KEPASTIAN HUKUM DALAM HAL PENGGANTIAN SERTIPIKAT MENJADI SERTIPIKAT ELEKTRONIK (SERTIPIKAT-EL) (Lex Jurnalica, 2022)
Proof of ownership of land is evidenced by the presence of certificates. This study aims to examine and understand aspects of legal certainty with the replacement of physical certificates with electronic certificates. This research method uses normative juridical. The issuance of Sertipikat-el can be pursued in terms of Land Registration for the First Time and Maintenance of Land Registration Data while still referring to the Basic Agrarian Law (UUPA) and PP 24/1997 which are implemented to ensure legal certainty in terms of proof by the community or at a trial. All matters relating to the Replacement of Certificates to Sertipikat-el will be carried out electronically so that all physical data and juridical data will be contained in an Electronic System. The replacement can be performed if the physical data and juridical data in the land book and the Certificate are appropriate. The confusion in society is related to legal certainty because it is regulated regarding the